2023
DOI: 10.3390/ijms241914806
|View full text |Cite
|
Sign up to set email alerts
|

To Break or Not to Break: The Role of TOP2B in Transcription

Ian G. Cowell,
John W. Casement,
Caroline A. Austin

Abstract: Transcription and its regulation pose challenges related to DNA torsion and supercoiling of the DNA template. RNA polymerase tracking the helical groove of the DNA introduces positive helical torsion and supercoiling upstream and negative torsion and supercoiling behind its direction of travel. This can inhibit transcriptional elongation and other processes essential to transcription. In addition, chromatin remodeling associated with gene activation can generate or be hindered by excess DNA torsional stress in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The DSBs that form on promoters of early response genes are mediated by Topoisomerase IIβ (TOP2B) [ 69 , 70 , 71 , 72 ]. Mutations of TOP2B lead to neurodevelopmental disorder and diastolic dysfunction [ 70 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ], which are phenotypically similar to when SMC5/6 components are mutated. Research using budding yeast and mammalian cell culture has shown that SMC5/6 and TOP2 physically and functionally interact [ 30 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DSBs that form on promoters of early response genes are mediated by Topoisomerase IIβ (TOP2B) [ 69 , 70 , 71 , 72 ]. Mutations of TOP2B lead to neurodevelopmental disorder and diastolic dysfunction [ 70 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ], which are phenotypically similar to when SMC5/6 components are mutated. Research using budding yeast and mammalian cell culture has shown that SMC5/6 and TOP2 physically and functionally interact [ 30 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…consistent with its involvement in replication and mitosis [12][13][14][15][16]. Top2B is more involved in chromatin modulation and remodeling during transcription [12][13][14]16,17]. Type II topoisomerases have been the targets of anticancer drugs for decades because disruption of topoisomerase activity leads to DNA damage and consequently cell death [11,18].…”
Section: Introductionmentioning
confidence: 99%
“…Top2A expression fluctuates with the cell cycle and is most highly expressed in S-phase and M-phase consistent with its involvement in replication and mitosis [ 12 , 13 , 14 , 15 , 16 ]. Top2B is more involved in chromatin modulation and remodeling during transcription [ 12 , 13 , 14 , 16 , 17 ]. Type II topoisomerases have been the targets of anticancer drugs for decades because disruption of topoisomerase activity leads to DNA damage and consequently cell death [ 11 , 18 ].…”
Section: Introductionmentioning
confidence: 99%